2020
DOI: 10.1186/s13028-020-0513-x
|View full text |Cite
|
Sign up to set email alerts
|

Herd-level risk factors for cow and calf on-farm mortality in Estonian dairy herds

Abstract: Background: On-farm mortality (unassisted death and euthanasia) is the unwanted loss of animals, and it comes with negative economic consequences. On-farm mortality rates reflect a herd's animal welfare status. The objective of this historical longitudinal single cohort study was to identify the associations between herd characteristics, animal housing conditions and management routines and within-herd calf and cow mortality rates in participating Estonian dairy herds. All farmers enrolled in the voluntary pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…Herds with ≤ 71 calves [OR= 0.85; p wald <0.05; CI 95 = 0.02, 0.33] and herds with >129 to ≤ 215 calves [OR= 0.74; p wald < 0.05; CI 95 = 0.02, 0.43] (compared with > 215 calves) were associated with decreased odds of diarrhea. Herd size has been described in other studies as a risk factor for diarrhea [ 20 ] and mortality in calves [ 21 , 22 ]. Klein-Jöbstl et al [ 20 ] explained that the association between diarrhea and greater herd size could be due to the insufficient caretakers on large-scale farms.…”
Section: Discussionmentioning
confidence: 99%
“…Herds with ≤ 71 calves [OR= 0.85; p wald <0.05; CI 95 = 0.02, 0.33] and herds with >129 to ≤ 215 calves [OR= 0.74; p wald < 0.05; CI 95 = 0.02, 0.43] (compared with > 215 calves) were associated with decreased odds of diarrhea. Herd size has been described in other studies as a risk factor for diarrhea [ 20 ] and mortality in calves [ 21 , 22 ]. Klein-Jöbstl et al [ 20 ] explained that the association between diarrhea and greater herd size could be due to the insufficient caretakers on large-scale farms.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of housing type were mixed or neutral in reference to mortality (Alvåsen et al, 2012;Popescu et al, 2014;Reimus et al, 2020), diarrhea (Mattiello et al 2009;Ostojić-Andrić et al 2011;Popescu et al 2014), and respiratory disorders (Mattiello et al, 2009;Ostojić-Andrić et al, 2011;Popescu et al, 2014). One of 4 studies addressing Johne's disease found a beneficial effect of tiestall housing on environmental prevalence of Mycobacterium avium ssp.…”
mentioning
confidence: 99%
“…There are no reports on the specific association between mortality of calves and immunization activity against respiratory diseases in calves. Vaccination for endemic bovine infections is described as a herd-level risk factor for the mortality of dairy cows ( McConnel, Lombard, Wagner, Kopral & Garry, 2015 ; Reimus, Alvåsen, Emanuelson, Viltrop & Mõtus, 2020 ; Reski-Weide, 2013 ). However, recent studies have described associations between management practices that focus on strengthening the immune system.…”
Section: Discussionmentioning
confidence: 99%